Smartphone addiction and anxiety in high school students – a cross-sectional study - Gultom, Rudolf L; Indrarto, FX Wikan; C.A Nugroho, Daniel; Siagian, Jonathan W (Universitas Gadjah Mada, 2021)
Purpose: Smartphones are a communication device that is widely used by people nowadays. Smartphones and their features have become a common need in the community. Excessive use of smartphones could lead to addiction. Smartphone addiction could affect physical and mental health. This study aims to assess the correlation between smartphone addiction and the level of anxiety among high school students. Method: This survey examined the correlation between smartphone addiction and anxiety in tenth-grade students of Frater Don Bosco High School (n=130) of Banjarmasin. Variables are measured using Smartphone Addiction Scale and Beck Anxiety Inventory. Data were then analyzed using proper correlation analysis. Result: Spearman's analysis shows that smartphone addiction had a relationship with anxiety (P: <0.001 and R 0.404). Whereas no significant correlations between age, sex, and lifestyle (smoking, alcohol, physical activity, sleep) with anxiety.